Specific Manifestations of Neurotoxicity of Some Drug Combinations for Treatment of Drug Resistant Tuberculosis from the Perspective of Experimental Studies - G. N. Mozhokina; A. G. Samoylova; I. A. Vasilyeva; I. A. Burmistrova (Туберкулез и болезни лёгких)
The objective: to evaluate comparative neurotoxicity of combinations of anti-tuberculosis and antimicrobial drugs with different and similar toxic potentials assessing behavioral changes in rats.Subjects and Methods: non-linear female rats divided in 3 groups were used in this study. For 14 days, the rats received a daily combinations of drugs: Group 1 – Mxf + Lzd + Cs + Pto, Group 2 – Mxf + Bdq + Cs + Z , and Group 3 – Bdq + Lzd + Cfz + Z. Neurotoxicity was assessed by changes in behavioral responses using Open Field Test. The number of crossed squares and racks was recorded which characterized horizontal and vertical activity, also peeping into burrows (exploratory activity), the number of groomings (washing and scratching) and physiological functions were registered.Results. In rats of Group 1 versus baseline parameters, we observed a significant limitation of horizontal motor activity and a sharp decrease (by 5 times) in exploratory activity, a 2.8-fold decrease in the number of groomings which indicated emotional suppression. In rats of Groups 2 and 3, the decrease in motor and exploratory activity was insignificant but there was a more pronounced emotional depression. The use of the Mxf + Lzd + Cs + Pto combination in which all drugs possessed a neurotoxic potential, led to diverse and profound changes in behavioral responses which indicated a pronounced neurotoxic effect.